Pembiasaan perilaku hidup bersih dan sehat di lingkungan PAUD - imamah, maulidatul (Maliki Interdisciplinary Journal, 2026)
This study aims to describe the importance of cultivating Clean and Healthy Living Behavior (PHBS) in early childhood and to identify effective strategies that can be implemented in early childhood education (PAUD) settings. The focus of the review is directed toward strengthening habits related to personal hygiene, environmental cleanliness, nutritious food selection, and children’s involvement in activities that support holistic health. The research method employed is a literature review with data sources derived from journals, early childhood education books, policy documents, and relevant previous studies. The findings indicate that cultivating PHBS during early childhood plays a significant role in shaping character, increasing immunity, and supporting children’s physical, cognitive, and socio-emotional development. Young children more easily understand hygiene concepts through hands-on practice, educational games, and creative strategies such as project-based learning, which allows them to actively participate in everyday health-related activities. The family, school, and community environments contribute greatly to the success of PHBS implementation by providing good role models, adequate sanitation facilities, and consistent routines. These findings emphasize that cultivating PHBS is not merely a basic health activity but also a long-term investment in building a healthy, independent, disciplined, and responsible generation. This study is expected to serve as a reference for educators, parents, and policymakers in designing effective and sustainable PHBS programs in early childhood education settings.